Improving Adherence to Secondary Stroke Prevention Strategies Through Motivational Interviewing - Barker-Collo, S; Krishnamurthi, R; Witt, E; Feigin, V; Jones, Amy; McPherson, K; Starkey, N; Parag, V; Jiang, Y; Barber, A; Rush, E; Bennett, D; et al. (American Heart Association, Inc., 2015)
Background and Purpose—Stroke recurrence rates are high (20%–25%) and have not declined over past 3 decades. This study tested effectiveness of motivational interviewing (MI) for reducing stroke recurrence, measured by improving adherence to recommended medication and lifestyle changes compared with usual care. Methods—Single-blind, prospective phase III randomized controlled trial of 386 people with stroke assigned to either MI treatment (4 sessions at 28 days, 3, 6, and 9 months post stroke) or usual care; with outcomes assessed at 28 days, 3, 6, 9, and 12 months post stroke. Primary outcomes were change in systolic blood pressure and low-density lipoprotein cholesterol levels as indicators of adherence at 12 months. Secondary outcomes included self-reported adherence, new stroke, or coronary heart disease events (both fatal and nonfatal); quality of life (Short Form-36); and mood (Hospital Anxiety and Depression Scale). Results—MI did not significantly change measures of blood pressure (mean difference in change, −0.2.35 [95% confidence interval, −6.16 to 1.47]) or cholesterol (mean difference in change, −0.0.12 [95% confidence interval, −0.30 to 0.06]). However, it had positive effects on self-reported medication adherence at 6 months (1.979; 95% confidence interval, 0.98–3.98; P=0.0557) and 9 months (4.295; 95% confidence interval, 1.56–11.84; P=0.0049) post stroke. Improvement across other measures was also observed, but the differences between MI and usual care groups were not statistically significant. Conclusion—MI improved self-reported medication adherence. All other effects were nonsignificant, though in the direction of a treatment effect. Further study is required to determine whether MI leads to improvement in other important areas of functioning (eg, caregiver burden). Clinical Trial Registration—URL: http://www.anzctr.org.au. Australian Clinical Trials Register (ACTRN-12610000715077).
Keywords: Recurrent stroke; Secondary prevention; Motivational interviewing; Adherence